Abdominal pain with a twist: a rare presentation of acute gastric volvulus. Issue 5 (13th October 2017) - Chen, David P.; Walayat, Saqib; Balouch, Imran L.; Martin, Daniel K.; Lynch, Teresa J.
ABSTRACT: Acute gastric volvulus is a life threatening condition requiring early diagnosis and aggressive management. Diagnosis of gastric volvulus remains a challenge for clinicians due to variable, non-specific clinical presentation, which requires a high level of suspicion. It should be considered in patients presenting with chest pain and/or epigastric pain, especially in the elderly population. Endoscopic de-rotation could be initially attempted as a therapeutic modality especially in patients who cannot undergo surgery. However, surgery remains the main stay of treatment. Delay in diagnosis can lead to complications like mucosal ischemia, necrosis or perforation, shock, which substantially increase the morbidity and mortality.